E-Supply Chain (e-SC) trust model for B2B collaboration- A case study of Malaysian construction industry - Aziz, N.B.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Lack of trust among the supply chain (SC) components has been identified as one of the issues that hinder collaboration between them. Thus, the focus of this study is to propose a trust model that helps to identify the trusted partner for B2B SC collaboration. In other words, this study aims to enable the trusted SC components collaborate in a trustful business environment. This can be achieved by using the trust model proposed. The trust model can be considered as guidelines to select a trusted trading partner. In addition, this study provides trust values identified according to domain chosen. The e-Supply Chain (e-SC) trust model proposed consider as solution to collaborate SC components. Â© 2014 IEEE.